2016
DOI: 10.1108/jes-11-2013-0169
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between self-employment and unemployment in the long-run

Abstract: Although a lot of research has been done on the link between selfemployment and unemployment, often focusing on the short-run of the relationship, the long-run association between the two variables has not received adequate attention. In this paper we examine the long-run relationship between self-employment and unemployment using panel cointegration methods allowing for structural breaks and covering a wide range of European OECD countries using the COMPENDIA dataset over the period 1990-2011. Our findings in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 81 publications
(140 reference statements)
0
7
0
Order By: Relevance
“…Other studies on self-employment have suggested that social isolation, a well-documented risk factor for suicide (Arango et al, 2016), is a substantial concern among those who are self-employed (Feldman & Bolino, 2000; Grant & Ferris, 2012). Some research also suggests that self-employment may be a marker of economic isolation in communities, in that poor economic conditions and unemployment may “push” individuals into self-employment as an alternative particularly if they experience other social risk factors such as low educational attainment (Earle & Sakova, 2000; Saridakis et al, 2016; Svaleryd, 2015), although other studies have shown mixed findings on this link (Henley, 2017). Other factors directly or indirectly linked to both self-employment and suicide such as stress, risk for financial loss, rural region, and access to lethal means may also potentially contribute to this association (Benach et al, 2004; Dolinsky & Caputo, 2003; Jamal, 2007; Stallones, Doenges, Dik, & Valley, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies on self-employment have suggested that social isolation, a well-documented risk factor for suicide (Arango et al, 2016), is a substantial concern among those who are self-employed (Feldman & Bolino, 2000; Grant & Ferris, 2012). Some research also suggests that self-employment may be a marker of economic isolation in communities, in that poor economic conditions and unemployment may “push” individuals into self-employment as an alternative particularly if they experience other social risk factors such as low educational attainment (Earle & Sakova, 2000; Saridakis et al, 2016; Svaleryd, 2015), although other studies have shown mixed findings on this link (Henley, 2017). Other factors directly or indirectly linked to both self-employment and suicide such as stress, risk for financial loss, rural region, and access to lethal means may also potentially contribute to this association (Benach et al, 2004; Dolinsky & Caputo, 2003; Jamal, 2007; Stallones, Doenges, Dik, & Valley, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Self-employment was measured as the percentage of workers that were self-employed. Self-employment has been linked to health and quality of life concerns such as stress, fatigue, and negative behavioral, psychological, and physical health outcomes (Benach, Gimeno, Benavides, Martinez, & del Mar Torné, 2004; Dolinsky & Caputo, 2003) as well as other social and economic characteristics that could potentially be linked to violence outcomes (Earle & Sakova, 2000; Saridakis, Mendoza, Muñoz Torres, & Glover, 2016; Svaleryd, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In this context, along with political analysis, many studies have tried to explore the counter- or pro-cyclical relationship between unemployment and entrepreneurship with a focus on developed and industrialised economies, rather than developing economies. However, the previous studies produced mixed and inconclusive results (Saridakis et al (2016). The unemployment-entrepreneurship nexus has important implications for governments in several crucial aspects.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, as different countries can be undergoing different periods of an economic (labor market) cycle, they may show different results of the interdependence between unemployment and self-employment. For instance, by employing panel cointegration methods, [9] investigated the COMPENDIA dataset, developed for a wide range of European OECD countries over the period 1990-2011. The results of their study disclosed a positive and statistically significant long-term relation between unemployment and self-employment which was observed in more than half of the countries under consideration.…”
Section: Source: Compiled By the Authorsmentioning
confidence: 99%
“…Previous studies that focused on the dynamic relationship between unemployment and self-employment in different countries provide rather contradictory results: depending on the recession push or entrepreneurial pull approach followed, some authors [6][7][8][9] found a positive and statistically significant relationship between the two phenomena under research, while others reported about a negative [10][11][12] insignificant [13] relationship or the existence of the relationship was not confirmed, especially as far as it concerns particular countries [14].…”
Section: Introductionmentioning
confidence: 99%